Identifying enablers and barriers to referral, uptake and completion of lifestyle modification programmes: a rapid literature review. Issue 3 (26th March 2021) - Zurynski, Yvonne; Smith, Carolynn; Siette, Joyce; Nic Giolla Easpaig, Bróna; Simons, Mary; Knaggs, Gilbert Thomas
Abstract : Objective: To identify current, policy-relevant evidence about barriers and enablers associated with referral, uptake and completion of lifestyle modification programmes (LMPs) for secondary prevention of chronic disease in adults. Design: A rapid review, co-designed with policymakers, of peer-reviewed and grey literature using a modified Preferred Reporting Items for Systematic Reviews and Meta-Analyses framework. Data sources: Medline, Embase, Scopus, PsycINFO and CINAHL were searched for relevant studies and literature reviews. Grey literature was identified through Advanced Google searching and targeted searching of international health departments' and non-government organisations' websites. Eligibility criteria for selecting studies: Documents published 2010–2020, from high-income countries, reporting on programmes that included referral of adults with chronic disease to an LMP by a health professional (HP). Data extraction and synthesis: Data from grey and peer-reviewed literature were extracted by two different reviewers. Extracted data were inductively coded around emergent themes. Regular meetings of the review group ensured consistency of study selection and synthesis. Results: Twenty-nine documents were included: 14 grey literature, 11 empirical studies and four literature reviews. Key barriers to HPs referring patients included inadequate HP knowledge about LMPs, perceptions of poor effectiveness of LMPs and perceptions that referral to LMPs was not part of their role. Patient barriers to uptake and completion included poor accessibility and lack of support to engage with the LMPs. Enablers to HP referral included training/education, effective interdisciplinary communication and influential programme advocates. Support to engage with LMPs after HP referral, educational resources for family members and easy accessibility were key enablers to patient engagement with LMPs. Conclusions: Factors related to HPs' ability and willingness to make referrals are important for the implementation of LMPs, and need to be coupled with support for patients to engage with programmes after referral. These factors should be addressed when implementing LMPs to maximise their impact.